Efeito da urbanização na Amazônia Meridional sobre o balanço de energia e a evapotranpiração por sensoriamento remoto - Pinheiro, Jean Reinildes (2016)
The colonization process in the Amazon, which occurred in the early 70s contributed to the constant changes in coverage and land use. These changes due to the replacement of forest areas for urban area, has great influence on the hydrological cycle and the local climate. Thus, derived from orbital sensors data is an alternative to obtain surface information with wide spatio-temporal coverage of energy and evapotranspiration flows. In this context, this study aimed to analyze the effect of urbanization in the southern Amazon on the energy balance and evapotranspiration. The study was conducted with multispectral images TM/Landsat 5 for the urban area of the municipality of Sinop with temporal variation from 1985 to 2010. In this way it was possible to analyze the spatial and temporal pattern of energy flows and daily evapotranspiration and also assess the estimates made by the SEBAL for the different classes of land use, which was validated with data obtained by the method of eddy covariance. The results showed that in SEBAL validate the instantaneous radiation and daily balances were the parameters that showed best agreement between the estimated and measured data. The values in the Rn24 h, LE and H were overestimated, while the values G24 h, Rn24h and ET24h were underestimated. Between land use classes, the dense vegetation class fell by 110,2 km2 in their area, while the altered region class there was an increase of 96,7 km2 . All parameters analyzed showed different responses for different land uses to which caused an increase in albedo (0,02), temperature increase of the surface (7,6°C), increase of the heat flow in soil (21,5 W m-2 ), increasing the sensible heat flow (185,1 W m-2 ), reduction in NDVI (0,22 m 2 m -2 ), reducing the flow of latent heat (206,4 W m-2 ) and therefore decrease in daily evapotranspiration (2,1 mm d-1 ). The percentage of Rn followed the pattern observed for use and occupation, which for the year 1985 the highest percentage of Rn was intended for latent heat flux, while in 2010 the highest percentage was allocated to sensible heat flux.